Extrahepatic cancers are the leading cause of death in patients achieving hepatitis B virus control or hepatitis C virus eradication. Issue 4 (10th July 2018) - Allaire, Manon; Nahon, Pierre; Layese, Richard; Bourcier, Valérie; Cagnot, Carole; Marcellin, Patrick; Guyader, Dominique; Pol, Stanislas; Larrey, Dominique; De Lédinghen, Victor; Ouzan, Denis; Zoulim, Fabien; et al.
Abstract : Data on extrahepatic cancers (EHCs) in compensated viral cirrhosis are limited. The objective of the prospective multicenter Agence Nationale de Recherche sur le SIDA et les Hépatites virales CO12 CirVir cohort was to assess the occurrence of all clinical events in patients with compensated viral cirrhosis, including all types of cancer. Patients with the following inclusion criteria were enrolled in 35 French centers: (1) biopsy‐proven hepatitis B virus (HBV) or hepatitis C virus (HCV) cirrhosis, (2) Child‐Pugh A, or (3) absence of previous liver complications including primary liver cancer (PLC). Patients were followed up prospectively every 6 months. The standardized mortality ratio (SMR) was calculated according to age and gender using 5‐year periods. The impact of sustained viral response (SVR) in HCV patients and maintained viral suppression in HBV patients were assessed using time‐dependent analysis. A total of 1, 671 patients were enrolled between 2006 and 2012 (median age, 54.9 years; men, 67.3%; HCV, 1, 323; HBV, 317; HCV–HBV, 31). Metabolic features and excessive alcohol and tobacco consumption were recorded in 15.2%, 36.4%, and 56.4% of cases, respectively. After a median follow‐up of 59.7 months, 227 PLCs were diagnosed (5‐year cumulative incidence [CumI] 13.4%) and 93 patients developed EHC (14 patients with lymphoid or related tissue cancer and 79 with solid tissue cancer; 5‐year EHC CumI, 5.9%). Compared to the general French population, patients were younger at cancer diagnosis, with significantly higher risk of EHC in HCV patients (SMR, 1.31; 95 confidence interval [CI], 1.04‐1.64; P = 0.017) and after SVR (SMR = 1.57; 95% CI, 1.08‐2.22; P = 0.013). EHC was the fourth leading cause of death in the whole cohort and the first in patients with viral control/eradication. Conclusion : Compared to the general French population, HCV cirrhosis is associated with a higher risk of EHC and the first cause of death in patients with viral cirrhosis who achieve virological control/eradication. (Hepatology 2018).